The system of political and administrative corruption in a West Malaysian state - Sivalingam, G. (Philippine Journal of Public Administration, 1991)
The Weberian master concept of sultanism argues that political and administrative corruption and high- and low-level corruption are not distinct forms of corruption but are interrelated. An estimate of the magnitude of reported corruption is followed by a discussion of types of corruption at different levels in the state bureaucracy. The final section focuses on the differences between the formal Weberian legal-rational type of bureaucracy and sultanism explaining why and describing how corrupt bureaucrats are protected in a system where the indigenous bureaucracy has become dominant and powerful.